1993
DOI: 10.1159/000213540
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Increased Longevity in <i>Drosophila melanogaste</i><i>r</i>: A New Interpretation

Abstract: The study of the genetic determinism of longevity in Drosophila melanogaster has made use of the technique of late-age reproduction. At low larval density, that indirect selection showed no effect. At high larval density, however, increased mean life-span in lines reproduced at late age was observed. When these last data are examined as a function of the number of days after the beginning of the experiment, instead of as a function of generations, the difference in life-span between early and late lines at hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Baret and Lints [2] have recently reexam ined those data, and suggest a new interpreta tion. When selected and control lines are com pared on the basis of days since initiation of the experiment, rather than generation num bers, then the putative selection response dis appears.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Baret and Lints [2] have recently reexam ined those data, and suggest a new interpreta tion. When selected and control lines are com pared on the basis of days since initiation of the experiment, rather than generation num bers, then the putative selection response dis appears.…”
Section: Introductionmentioning
confidence: 81%
“…observa tion], the concerns of Baret and Lints [2] about comparing means estimated at differ ent times is justifiable. To anwer their con cerns directly, one could test the control and selected lines simultaneously in a common controlled environment.…”
Section: Age (Days)mentioning
confidence: 99%
“…The flies of the the second group senesce more slowly and live up to 50% longer than the first group flies (Baret & Lints, 1993;Fukui et al, 1995;Luckinbill & Clare, 1985;Rose & Charlesworth, 1980;1981).…”
Section: Findings Supporting Each Evolutionary Theorymentioning
confidence: 99%
“…As a result of the work of many laboratories on sev eral different model systems, there is no lon ger any doubt that longevity and senescence are under some form of genetic control [2], In the case of Drosophila, this statement is based on evidence obtained from a variety of studies using single gene mutants, transgenic animals, and/or selected strains. Several laboratories have used various reproductive selection schemes to derive genetically selected longlived and/or short-lived strains from a progen itor baseline, and have interpreted their re sults as a conclusive demonstration that lon gevity is a malleable phenotype amenable to genetic analysis [3][4][5][6][7], In a recent communication, Baret and Lints [8] have reinterpreted certain selected strain data in an effort to demonstrate a dis senting view: namely, that '... the mean longe vities of a series of lines, presumably geneti cally different -if we admit that indirect selection by late reproduction has some effect on the gene pool -do not differ after 21 gener ations of selection' [8, p. 257], that '... the dif ferences between lines may be explained simply by the time lag in the measurements of the longevity' [8, p. 259], and thus that 'kind of experiment appears now to be irrelevant to Introduction test the genetic determinism of longevity in D. melanogaster' [8, p. 259], They arrived at this conclusion by taking a limited set of data from the experiments of Lints and Hoste [9], Luckinbill et al [4] and from Luckinbill and Clare [10], and then replotted the calculated mean longevities as a function of the number of days elapsed since the beginning of the selection experiment, rather than by the more conventional method of plotting the longevi ties as a function of the number of generations elapsed since the initiation of selection. Their rationale for adopting this new procedure is to compensate for the time lag that inevitably appears between the measurements of a given generation in early or late lines.…”
mentioning
confidence: 99%
“…They have thus raised an important point which must be conclusively settled one way or the other. Baret and Lints [8] presumably have free access to the data from the Lints and Hoste [9] experiment, but must obviously rely on only published data for their reinterpretation of the Luckinbill and Clare [10] experiments. As coninvestigators in the original investigation in which we reported the successful creation of genetically selected lines with different lon gevities [4], and as an independent team in vestigating the genetics of aging in Drosophila since that time [see 11 for review and refer ences], we feel scientifically obliged to reex amine all of our data in light of the criticisms of Baret and Lints [8].…”
mentioning
confidence: 99%